Optical Reflex Treatment of Myopia and Asthenic Form of Accommodation Asthenopia Form the Standpoint of the Methods Used, Effectiveness and Staging - I. G. Ovechkin (Oftalʹmologiâ, 2020)
Optical-reflex treatment of patients with myopia and computer visual syndrome with a concomitant asthenic form of accommodation asthenopia seems relevant and not fully developed. The basic provisions that determine the tactics of treatment are monocular exposure in order to increase the absolute accommodation rate and staging (outpatient room, home conditions) of training. Measures aimed at improving the effectiveness of optical reflex treatment at home include the development of alternative instrumentation with reasonable (in accordance with the clinical and physiological characteristics of the functioning of the ciliary muscle of the eye) optical, amplitude and temporal parameters of the training process.